2003
DOI: 10.1002/gps.924
|View full text |Cite
|
Sign up to set email alerts
|

The needs of older people with mental health problems according to the user, the carer, and the staff

Abstract: User perspectives should be given a high priority when assessing individual needs. Fears that assessment of need would be unduly time-consuming or would simply reflect individual demands should be allayed. A user-based assessment will assist healthcare providers to prioritise needs according to what the user themselves consider to be most important, beneficial, and acceptable to them. Reliance solely on assessment by staff or carers may not lead to the most equitable or appropriate use of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 20 publications
(44 reference statements)
12
57
3
2
Order By: Relevance
“…It is unclear from this study how many of these needs were met/unmet. Hancock et al (2003) found that patients with dementia rated fewer needs (both met and unmet) compared to their carers or relevant staff members, whereas patients with functional disorders rated similar numbers of needs to staff and carers. This under reporting of needs (both met and unmet) by people with dementia may be due to a number of reasons such as memory problems, lack of insight, denial or resignation.…”
Section: Introductionmentioning
confidence: 95%
“…It is unclear from this study how many of these needs were met/unmet. Hancock et al (2003) found that patients with dementia rated fewer needs (both met and unmet) compared to their carers or relevant staff members, whereas patients with functional disorders rated similar numbers of needs to staff and carers. This under reporting of needs (both met and unmet) by people with dementia may be due to a number of reasons such as memory problems, lack of insight, denial or resignation.…”
Section: Introductionmentioning
confidence: 95%
“…Os resultados obtidos no presente estudo são sensíveis aos dados descritos anteriormente, apresentando uma prevalência algo superior aos valores estimados para a população idosa em geral, uma vez que foram obtidos a partir de uma amostra de pessoas em regime de internamento psiquiátrico. Contudo, estão muito próximos de outros estudos em populações psiquiátricas (Gonçalves-Pereira et al, 2007;Fernandes et al, 2009;Hancock, Reynolds, Woods, ornicro & Orrell, 2003;Mateos, Ybarzábal, Garcia, Amboage & Fraguela, 2004;Reynolds et al, 2000). No que diz respeito aos focos de atenção de enfermagem identi cados, veri cou-se também uma aproximação em relação aos dados disponíveis.…”
Section: Discussão Dos Resultadosunclassified
“…Previous research compared staff members' and patients' need perceptions [7][8][9][10][11]. Other studies conversely examined patients' and family members' perceptions [13], and only a few studies have compared the views of patients, staff and family members of needs for care [12,14,34,35]. Most of the latter studies, however, were conducted in geriatric settings [14,34,35], not in mental health facilities serving the adult population.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
“…Other studies conversely examined patients' and family members' perceptions [13], and only a few studies have compared the views of patients, staff and family members of needs for care [12,14,34,35]. Most of the latter studies, however, were conducted in geriatric settings [14,34,35], not in mental health facilities serving the adult population. Moreover, the only study comparing the views of staff member', patients and relatives [12] specifically focused on needs for care, without addressing service satisfaction.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation